The cross-cultural look of assistance provided to the population in street conditions at COVID-19 (Research, Society and Development, 2022)
COVID-19 is an infection caused by the coronavirus that in the year 2020 took global proportions. In view of this, several policies were implemented in order to repress and minimize the spread of the virus, especially the care provided to homeless populations in the context of the pandemic and actions that promote a universal balance of the human being. This article is an integrative literature review, structured in 6 steps in order to gather and synthesize information on a topic. From the studies found, the inclusion and exclusion criteria were carried out and only 16 articles answered the guiding question "which studies published in 2019 and 2020 that address the assistance provided to homeless people in the COVID 19 pandemic?"''. In addition, it is noted that research shows that the measures developed do not take into account the cultural context, values ​​and lifestyle of these individuals. There is a need for literature that addresses the view of the homeless population in relation to the assistance provided, in order to know their individualities. In addition, it is important to relate the transcultural theory in the context of the homeless population for the production not only of a humanized knowledge, but also for the elaboration of a culturally specific care that respects the lifestyle of this population.